Lactobacillus plantarum as a probiotic in the initial development of juvenile fat snook - de Souza, Rodrigo Matos; Sugai, Juliet Kiyoko; Mouriño, José Luiz Pedreira; Cerqueira, Vinicius Ronzani (Arquivos de Ciências do Mar, 2018)
With great potential for aquaculture, the fat snook need technologies for mass production of fingerling with high-quality for pre-ongrowing. One way of obtaining better results with healthy and resistant fish would be the use of probiotics. It was verified the influence of Lactobacillus plantarum supplementation to juvenile diet (56 days after eclosion) on growth, survival, activity of digestive proteases and resistance hypersaline stress. The test of 30 days was composed of three treatments, the first being exclusively fed with Artemia and the two feeding transition received for 15 days and Artemia feed with one of supplementation with L. plantarum and after exclusively the respective feed. The results indicate that bacterial supplementation during dietary transition resulted in increased alkaline protease activity in the digestive tract of fat snook juveniles, as well as increased resistance to salt stress, indicating fish better and healthier, assisting in production massive juvenile fat snook with high quality and ready for storage in pre-ongrowing system.